Effects of Two Commonly Found Strains of Influenza A Virus on Developing Dopaminergic Neurons, in Relation to the Pathophysiology of Schizophrenia - Landreau, Fernando (2012)
Influenza virus (InfV) infection during pregnancy is a known risk factor for neurodevelopment abnormalities in the offspring, including the risk of schizophrenia, and has been shown to result in an abnormal behavioral phenotype in mice. However, previous reports have concentrated on neuroadapted influenza strains, whereas increased schizophrenia risk is associated with common respiratory InfV. In addition, no specific mechanism has been proposed for the actions of maternal infection on the developing brain that could account for schizophrenia risk. We identified two common isolates from the community with antigenic configurations H3N2 and H1N1 and compared their effects on developing brain with a mouse modified-strain A/WSN/33 specifically on the developing of dopaminergic neurons. We found that H1N1 InfV have high affinity for dopaminergic neurons in vitro, leading to nuclear factor kappa B activation and apoptosis. Furthermore, prenatal infection of mothers with the same strains results in loss of dopaminergic neurons in the offspring, and in an abnormal behavioral phenotype. We propose that the well-known contribution of InfV to risk of schizophrenia during development may involve a similar specific mechanism and discuss evidence from the literature in relation to this hypothesis.